Clinical characteristics of very old patients hospitalized in internal medicine wards for heart failure: a sub-analysis of the FADOI-CONFINE Study Group - Paolo Biagi; Roberto Nardi; Concetta Isabella Baldo; Giovanni Scanelli; Domenico Panuccio; Andrea Bonanome; Fabio Miserocchi; Luigi Lusiani; Erminio Bonizzoni; Mauro Campanini; Carlo Nozzoli; Giorgio Vescovo; et al. (Italian Journal of Medicine, 2014)
The incidence and prevalence of chronic heart failure are increasing worldwide, as is the number of very old patients (>85 years) affected by this disease. The aim of this sub-analysis of the multicenter, observational CONFINE study was to detect clinical and therapeutic peculiarities in patients with chronic heart failure aged >85 years. We recruited patients admitted with a diagnosis of chronic heart failure and present in the hospital in five index days, in 91 Units of Internal Medicine. The patients’ clinical characteristics, functional and cognitive status, and the management of the heart failure were analyzed. A total of 1444 subjects were evaluated, of whom 329 (23.1%) were over 85 years old. Signs and symptoms of chronic heart failure were more common in very old patients, as were severe renal insufficiency, anemia, disability and cognitive impairment. The present survey found important age-related differences (concomitant diseases, cognitive status) among patients with chronic heart failure, as well as different therapeutic strategies and clinical outcome for patients over 85 years old. Since these patients are usually excluded from clinical trials and their management remains empirical, specific studies focused on the treatment of very old patients with chronic heart failure are needed.